KEPEMIMPINAN TERDISTRIBUSI DAN DAMPAKNYA TERHADAP SEKOLAH: TINJAUAN LITERATUR - Ina Marlina; Yudi Ekka Suryapriadi; Priatna, Asep (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This literature review synthesizes recent empirical research on distributed leadership and its impact on schools, with a focus on student achievement, teacher outcomes, and organizational effectiveness. A narrative review approach was used to provide a thematic synthesis of findings and theoretical developments. Data were retrieved from the Scopus database using the search strings TITLE (distributed AND leadership) AND TITLE (school), yielding 197 peer-reviewed journal articles. After applying inclusion criteria focusing on English-language publications and journal articles, 35 studies were selected for in-depth qualitative analysis. The review differentiates between structural and functional distributed leadership and finds that a functional approach emphasizing collaboration and shared decision-making produces more consistently positive outcomes. Evidence suggests that distributed leadership improves student performance and teacher professional growth through mediating factors such as teacher collaboration, organizational trust, and professional learning communities. However, challenges remain, including unclear role boundaries, resistance to authority changes, and cultural barriers within hierarchical school systems. The review highlights the need for context-sensitive implementation supported by professional development and a collaborative organizational culture. Future research should expand longitudinal and cross-cultural studies to better understand how distributed leadership develops over time and operates in diverse educational contexts.